Trauma Exposure and Prolonged Grief Disorder Among Persons Receiving Community Mental Health Services: Rates and Correlates - Lu, Weili; Yanos, Philip T.; Waynor, William R.; Gao, Carol E.; Bazan, Carolyn; Giacobbe, Giovanna; Gill, Kenneth; Bullock, Deanna; Prigerson, Holly G. (Frontiers in Psychiatry, 2022)
Background: Persons with serious mental illnesses (SMIs) are at increased risk for exposure to trauma and posttraumatic stress disorder (PTSD). Prolonged Grief Disorder (PGD) may also impact this population but has been seldom studied. Aims: The present study investigated the rate of both PTSD and PGD among clients receiving community mental health services, and the clinical correlates of co-occurring PTSD/PGD. Methods: Trauma history, PTSD and PGD were assessed among 536 individuals receiving community mental health services (Study 1). A subsample of 127 individuals from Study 1 who met DSM-5 criteria for PTSD based on diagnostic interview completed measures of psychiatric symptoms (Study 2). Results: In Study 1, 92.4% of participants receiving community mental health services had experienced a traumatic event, 49.6% met criteria for probable and provisional PTSD, 14.7% scored positive for probable PGD, and 11.9% met criteria for probable and provisional PTSD as well as probable PGD. In Study 2, participants meeting diagnostic DSM-5 criteria for PTSD and probable PGD had more self-reported PTSD symptoms, but did not differ on other outcomes. Conclusions: Findings highlight the need for trauma informed services including grief counseling for persons with SMI.